A sustained high fat diet for two years decreases IgM and IL-1 beta in ageing Wistar rats - Pongratz, Georg; Bertsch, Thomas (Immunity & ageing, 2015)
The immune system undergoes several alterations of innate and adaptive immunity during ageing. The main features of the aged immune system are a reduced diversity of T cell receptors and a reduced activity of innate immune cells with subsequent changes in adaptive immunity resulting in a less effective, less specific, and dys-regulated immune response and in an increased susceptibility towards infection, malignancy, and autoimmunity. The process is referred to as immunosenescence and is also modulated by environmental modifiers, such as dietary factors. High fat diet (HFD), via direct modulation of immune cell function by fatty acids and/or increased body fat mass, influences immune function. However, it is not clear whether HFD is beneficial or detrimental for the functioning of the ageing immune system.
Gesehen am 19.11.2018